2004
DOI: 10.1007/s00276-004-0226-2
|View full text |Cite
|
Sign up to set email alerts
|

Relationships of the palmar cutaneous branch of the median nerve: a morphometric study

Abstract: Treatment of carpal tunnel syndrome consists in decompression of the median nerve by section of the flexor retinaculum. Usually, this surgery improves the disease with disappearance of the symptoms. However, some painful sequelae may remain such as painful discharges, paresthesiae or permanent anesthesia of the base of the thumb or of the scar related to an injury of the palmar cutaneous branch of the median nerve (PCBm). This study was performed to define the accurate emergence and the anatomic characteristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
0
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(49 citation statements)
references
References 14 publications
5
41
0
3
Order By: Relevance
“…1 and 2) was made distally to the proximal wrist crease, along a longitudinal line virtually drawn from the third finger web space to the wrist. 1,5 To our knowledge, the other minimally invasive techniques require larger incisions. After the skin was incised, a couple of retractors were placed perpendicular to the incision to expose a layer of subcutaneous fat.…”
Section: Double Tunnels Techniquementioning
confidence: 99%
See 2 more Smart Citations
“…1 and 2) was made distally to the proximal wrist crease, along a longitudinal line virtually drawn from the third finger web space to the wrist. 1,5 To our knowledge, the other minimally invasive techniques require larger incisions. After the skin was incised, a couple of retractors were placed perpendicular to the incision to expose a layer of subcutaneous fat.…”
Section: Double Tunnels Techniquementioning
confidence: 99%
“…Although the ligament was sliced blindly, it was performed within the safe zone according to the Martin classification. 1,5,23 To avoid iatrogenic damage to the nerves, it is enough to respect certain anatomical criteria. Watchmaker 35 et al showed that the palmar cutaneous branch of the median nerve appears 2.09 ± 0.31 cm from the distal wrist crease.…”
Section: Double Tunnels Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…This activity could be responsible for hypertrophy of the belly of the APLM, causing temporary compression of median nerve or of its palmar cutaneous branch. In fact, the usual site of emergence of the palmar cutaneous branch is located at about 4-5 cm from the bistyloid line (Chaynes et al, 2004) and the muscular belly was located in the distal third of the forearm. However, during the surgical 2.…”
Section: Discussionmentioning
confidence: 99%
“…It is located above the flexor retinaculum and passes between the tendons of the flexor carpi radialis and palmaris longus muscles (Chaynes et al 2004). The branch arises off the radial side of the median nerve along the radial edge of the flexor digitorum superficialis, 5-7 cm proximal to the wrist crease .…”
Section: Median Nervementioning
confidence: 99%